E-consumer protection in Malaysia: misleading information in advertisement - Mohd Nor, Roshazlizawati; Amin, Naemah (2014)
Advertising is widely used on the Internet either to promote goods sold or to entice consumer towards a particular web site, especially in e-commerce relating to business to consumer (B2C). Advertising is considered as a powerful promotional activity and its practices is the same as to face-to-face business. In e-commerce, the purpose of advertisement is to inform and at the same time allure e-consumers to the products as advertised by the e-sellers. In many situations, e-consumers are attracted to the content of advertisement and make their decisions to buy the products as advertised. This is because in the online purchasing, e-consumers cannot touch, even see or feel the goods before buying them. Therefore, most e-commerce sites will contain information which is relied upon by visitors to the site. Thus, the role of the law here is crucial in protecting the e-consumers from false, inaccurate and misleading information provided by the e-sellers who purposely to entice the e-consumers into concluding a contract. This paper will discuss how far the existing Malaysian law could protect the e-consumer from the misleading information and false advertisements done by bogus e-sellers. Therefore, this paper will evaluate several Malaysian related e-commerce legislations focusing on the protection for e-consumers in this issue namely the Trade description Act 2011, the Consumer Protection Act 1999 (Consumer Protection (Electronic Trade Transactions) Regulations 2012), the Sale of Goods Act 1957, the Contract Act 1950 and the Direct Sales and Anti-Pyramid Scheme Act 1993.